Non-coding RNAs as potential biomarkers and therapeutic targets in polycystic kidney disease - Zheng, Qi; Reid, Glen; Eccles, Michael R.; Stayner, Cherie (Frontiers in Physiology, 2022)
Polycystic kidney disease (PKD) is a significant cause of end-stage kidney failure and there are few effective drugs for treating this inherited condition. Numerous aberrantly expressed non-coding RNAs (ncRNAs), particularly microRNAs (miRNAs), may contribute to PKD pathogenesis by participating in multiple intracellular and intercellular functions through post-transcriptional regulation of protein-encoding genes. Insights into the mechanisms of miRNAs and other ncRNAs in the development of PKD may provide novel therapeutic strategies. In this review, we discuss the current knowledge about the roles of dysregulated miRNAs and other ncRNAs in PKD. These roles involve multiple aspects of cellular function including mitochondrial metabolism, proliferation, cell death, fibrosis and cell-to-cell communication. We also summarize the potential application of miRNAs as biomarkers or therapeutic targets in PKD, and briefly describe strategies to overcome the challenges of delivering RNA to the kidney, providing a better understanding of the fundamental advances in utilizing miRNAs and other non-coding RNAs to treat PKD.